2016
DOI: 10.1002/suco.201500044
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fatigue behaviour of CFRP plates externally bonded to concrete substrate

Abstract: The behaviour of the bond between fibre‐reinforced polymers (FRP) and concrete greatly influences the behaviour of concrete structures strengthened with FRP composites. Although numerous experimental studies have investigated this bond, experimental data concerning fatigue tests on carbon FRP plates attached to concrete blocks are still lacking. Therefore, a series of double‐lap shear tests under monotonic and fatigue loadings were performed on concrete prismatic specimens reinforced with CFRP plates. First, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Crack opening measurements have been performed each 10 kN load step. Records for PCFC_01 and PCFC_02 have been taken at preloading and after 30,000, 100,000, 1 million, and 5 million cycles 4,6,7,15,17,25,44–47 …”
Section: Methodsmentioning
confidence: 99%
“…Crack opening measurements have been performed each 10 kN load step. Records for PCFC_01 and PCFC_02 have been taken at preloading and after 30,000, 100,000, 1 million, and 5 million cycles 4,6,7,15,17,25,44–47 …”
Section: Methodsmentioning
confidence: 99%
“…More advanced S-N curve expressions involve a power function formula (double logarithmic formula) and exponential function formula (single logarithmic formula). However, previous studies have shown that fatigue life of FRP-concrete interfaces and stress level obey a single logarithmic formula [39,40]. We therefore also use a single logarithmic formula to characterize the S-N curve of the FRP grid-concrete interface (Figure 9).…”
Section: Loading Endmentioning
confidence: 99%
“…The database was collected from the existing literature [1,2,[10][11][12], which included different cross-sections, such as rectangular and box beams, strengthening configuration of full wrapping with strips or continuous sheets and U-shaped beams, and beams without internal stirrups. The values of the database were obtained from 6 beams with box cross section and 22 beams with rectangular cross-section.…”
Section: Database Collectionmentioning
confidence: 99%
“…Since the beginning of the present century, researchers have paid much attention to the torsional behavior of reinforced concrete (RC) beams strengthened with fiber-reinforced polymer (FRP) sheets by experimental investigation [1][2][3]; however, very few models exist to predict the ultimate strength of strengthened RC beams. The fib Bulletin 14 [4] proposed equations to calculate the ultimate torsional moment of strengthened beams involving two typical failure patterns, namely, FRP fracture and debonding.…”
Section: Introductionmentioning
confidence: 99%